Hardness removal from waters by using citric acid modified pine cone - Altundoğan, Hamdi Soner; Topdemir, Aykut; Çakmak, Meltem; Bahar, Nurdan (My University, 2016)
In this study, an effective cation exchanger was developed from pine cone by citric acid modification and its hardness removal properties from waters were investigated. For this purpose, grinded pine cone samples were subjected to a citric acid modification following NaOH saponification. Both of the raw and modified pine cone samples were subjected to standardized hardness removal tests by shaking with hard waters. These tests showed that citric acid modification significantly increases the cation exchange capacity of the pine cone. Also, most suitable size fraction of pine cone was determined as -16+30 mesh (600 um < x < 1200 um). Finally, citric acid modified product obtained from this fraction was used in a continuous system to remove hardness from water. The results of this study showed that citric acid-modified pine cone can be used to hardness removal from waters as a cheap and environment-friendly material.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Pine cone; Citric acid; Water hardness; Ion exchange; Cross-linking